2020
DOI: 10.3389/fmicb.2020.548620
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dual-Targeted α-Helical Peptide With Potent Antifungal Activity Against Fluconazole-Resistant Candida albicans Clinical Isolates

Abstract: Due to compromised immune system, fungal infection incidences have markedly increased in the last few decades. Pathogenic fungi have developed resistance to the clinically available antifungal agents. Antifungal resistance poses a great challenge to clinical treatment and has stimulated the demand for novel antifungal agents. A promising alternative to the treatment of fungal diseases is the use of antimicrobial peptides (AMPs). However, the antifungal activities of AMPs have not been fully determined. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…These polymers might act to trap the AMPs, facilitating the penetration of the cell wall [42]. Subsequently, the outer membrane permeability and cytoplasmic membrane depolarization induced by K65 and K70 rapidly increased and had significant time-and concentration-dependent effects, indicating that the peptide-membrane interaction might be related to channel or pore formation, thus leading to cellular component leakage and cell death [43]. Interestingly, depolarization of the S. aureus cytoplasmic membrane induced by the Feleucin-K3 analogs was weaker than that in Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These polymers might act to trap the AMPs, facilitating the penetration of the cell wall [42]. Subsequently, the outer membrane permeability and cytoplasmic membrane depolarization induced by K65 and K70 rapidly increased and had significant time-and concentration-dependent effects, indicating that the peptide-membrane interaction might be related to channel or pore formation, thus leading to cellular component leakage and cell death [43]. Interestingly, depolarization of the S. aureus cytoplasmic membrane induced by the Feleucin-K3 analogs was weaker than that in Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as described above, hydrolyzable tannins (Bueno et al, 2014) such as pyrogallol, ellagic acid, and gallic acid (Sereia et al, 2019) were identified in the EAF from P. pluviosa stem bark. The antifungal activity of all these compounds has already been described for different species of fungi (de Paula E Silva et al, 2014;Yang et al, 2020); besides, the immunomodulatory activity of polyphenols was also well-known (Ding et al, 2018). Particularly, gallic acid inhibits the growth of C. neoformans (de Paula E Silva et al, 2014) and can modulate the host innate immune response, increasing defense against microbial infections (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal activity of all these compounds has already been described for different species of fungi (de Paula E Silva et al, 2014;Yang et al, 2020); besides, the immunomodulatory activity of polyphenols was also well-known (Ding et al, 2018). Particularly, gallic acid inhibits the growth of C. neoformans (de Paula E Silva et al, 2014) and can modulate the host innate immune response, increasing defense against microbial infections (Yang et al, 2020). Therefore, the combined antivirulence and immunomodulatory activities of the polyphenols may be responsible for the therapeutic effect of EAF from P. pluviosa stem bark observed in G. mellonella infection in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of AMP-17 on membrane permeability was detected by flow cytometry, according to a previously described method, with minor modifications. 31 Briefly, C. neoformans cells were diluted to 1.0×10 6 CFU/mL. Cell suspensions were incubated for 6 h at 35 °C with 1, 2, and 4× MIC AMP-17.…”
Section: Methodsmentioning
confidence: 99%